IMPLEMENTASI KEPEMIMPINAN MANAJERIAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Evi Sayyidah; Taqwatul Uliyah; Riskun Iqbal (UNISAN JURNAL, 2023)
The purpose of this study is to reveal the implementation of the principal’s managerial leadership and teacher performance at UPT SMP Negeri 24 Bandar Lampung. This research the writer did using a qualitative approach. Data collection techniques were carried out by observation, interviews and documentation. The analysis used is non-statistical data analysis, namely analyzing data collected in interview transcripts, field notes and documents. It can be concluded that the implementation of the principal’s managerial leadership in improving teacher performance at UPT SMP Negeri 24 Bandar Lampung has been well implemented. The principal’s managerial leadership includes planning, the principal has carried out the vision and mission of the school, and has developed long-term plans and short-term plans for the school. Then, organizing (organizing), the principal has been able to implement and maintain a positive school climate. In controlling, it has been carried out by the school principal by: preparing a plan for supervision activities at the beginning of the year; teaching supervision is carried out on teaching plans and teaching implementation processes. Then, the performance of UPT SMP Negeri 24 Bandar Lampung teachers has been going well, in planning lessons, where teachers have been able to make learning tools such as lesson plans, semester programs, annual programs, KKM analysis, and other learning tools. In carrying out learning activities, the teacher has shown good performance, namely understanding seriously the material that has been prepared, having the ability to master the class, providing motivation and interest in learning, using appropriate methods, designing learning strategies and being able to provide and use learning media and utilization of learning resources. However, there are still a number of UPT SMP Negeri 24 Bandar Lampung teachers with a relatively low work ethic. The teacher’s low work ethic is caused by age, illness, and low mastery of technology.